2010
DOI: 10.1007/s12666-010-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of magnesium alloy ZM21

Abstract: Friction stir butt welding of Mg-Zn-Mn alloy ZM21 hot rolled plates (in three thicknesses -5 mm, 10 mm and 25 mm) was investigated. Defect-free, full-penetration welds were produced after careful process parameter optimization. Microstructural studies, hardness tests, tensile tests, and bend tests were carried out. Welds produced in 5 mm thick (5-mm-welds) and 10 mm thick plates (10-mm-welds) showed relatively finer grains in the weld nugget and in the heat-affected zone compared to the welds produced in 25 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Moreover, the elongation of the former is obviously decreased. The mechanical properties of several kinds of FSW Mg alloys [AZ31 (Yang et al, 2010;Xin et al, 2014;Ugender, 2018), AZ61 (Park et al, 2003b;Singh et al, 2018), ZK60 (Xie et al, 2008), ZM21 (Harikrishna et al, 2010), and Mg-Zn-Y-Zr (Xie et al, 2007)] were further summarized, as shown in Figure 4. It is seen that the YS and UTS of FSW Mg alloys are generally lower than that of BM.…”
Section: Properties and Deformation Mechanisms Of Fsw Mg Jointmentioning
confidence: 99%
“…Moreover, the elongation of the former is obviously decreased. The mechanical properties of several kinds of FSW Mg alloys [AZ31 (Yang et al, 2010;Xin et al, 2014;Ugender, 2018), AZ61 (Park et al, 2003b;Singh et al, 2018), ZK60 (Xie et al, 2008), ZM21 (Harikrishna et al, 2010), and Mg-Zn-Y-Zr (Xie et al, 2007)] were further summarized, as shown in Figure 4. It is seen that the YS and UTS of FSW Mg alloys are generally lower than that of BM.…”
Section: Properties and Deformation Mechanisms Of Fsw Mg Jointmentioning
confidence: 99%
“…These drawbacks are overcome by joining the Mg alloy plates through the Friction Stir Welding process (FSW). The cylindricalshouldered, normally non-consumable tool is allowed to travel along the contact line, and the rotation of the tool generates more heat due to the friction between the tool and the weld plates [37,38]. This heat is used to fabricate a grain refined and defect-free joint without reaching the melting point of the weld material.…”
Section: Introductionmentioning
confidence: 99%
“…It is a green metal and is considered to be the most environmentally friendly metal available for structural applications [5]. Despite being light in weight and having high specific strength, it has less ductility due to its HCP crystal structure [6,7].…”
Section: Introductionmentioning
confidence: 99%